Integrated coastal zone management in the Venice area: Potentials of the integrated participatory management approach - Frédéric Brochier; Carlo Giupponi; Julie Sors (Fondazione Eni Enrico Mattei (FEEM), 2001)
There is now a large consensus about the importance of actively involving stakeholders and local people for achieving a sound management of coastal zones. However, the nature and extent of public input is generally left to the discretion of local authorities and is often limited. In the Venice Lagoon in particular, the analysis of the local situation made clear some substantial lacks in co-ordination among the various administrative bodies in charge of planning and management at various scale and in different sectors. The paper aims to explore the concepts of participatory management and the tools, techniques and phases to implement it. In particular participation and collaboration issues are analysed with reference to the Integrated Coastal Zone Management (ICZM) context. The paper also examines specific requirements and constraints for the complex case of the Venice Lagoon System where participatory management should be initiated with limited demonstrative cases.
Keywords: D70; O21; Q20; 330; Venedig; Küstenschutz